(untitled) (Research, Society and Development, 2023)
Background: PHC services reflect poor working conditions and, in line with the COVID-19 pandemic, nurses end up being exposed to higher levels of stress. Objectives: To identify the level of perceived stress of PHC nursing workers during the COVID-19 pandemic. Methodology: Analytical cross-sectional study carried out in PHC units in a medium-sized Brazilian municipality. Questionnaires were applied to characterize socioeconomic, demographic, work and life habits of nursing workers and PSS-14 to 130 nursing workers. Data were entered and analyzed in the SPSS® software, version 22.0. Results: The PE, 27.5% of the nurses and 30.7% of the nursing technicians had, respectively, a normal and moderate level of PE. It was verified by the rho that PE was negatively correlated with the number of hours of sleep and hours of leisure. Conclusion: The results indicate the need for investment by the government so that these professionals have psychological support, quality of life and that there is no work overload aimed at the worker’s health.